Joseph Stiglitz: Globalization and its Discontents. (Czech Journal of International Relations, 2005)
Joseph Stiglitz: Globalization and its Discontents. 1st ed. London: Penguin Books, 2002, 281 stran, ISBN 0-713-99664-1 (signatura knihovny ÚMV 50 722).